FPGA Implementation of Inverse Fast Fourier Transform in Orthogonal Frequency Division Multiplexing Systems - Mohammady, Somayeh; Sulaiman, Nasri; Sidek, Roslina M.; Varahram, Pooria; Hamidon, M. Nizar (IntechOpen, 2012)
None